Robert B. Parker's buzz kill - Gaylin, Alison; Parker, Robert B., 1932-2010 (Parker, Robert B., 1932-2010. Sunny Randall novels, 2024)
After a near-death experience, Sunny Randall is ready to lighten her load as a PI, that is until she is called upon by billionaire media magnate Bill Welch to investigate the disappearance of his son, Dylan, the cofounder of the Gonzo Energy Drink company.